Transnational Coalition Building: The Role of The Yes I Do Alliance in Preventing Child Marriage Practices in Kediri Village, West Lombok - Ramli, St. Amaliah (Jurnal Hubungan Internasional, 2023)
The practice of child marriage is an impact of gender-based discrimination, which reduces the value of women. Such discrimination might violate children’s rights under the Convention on the Rights of the Child. Traditional Sasak marriages, known as Merariq, are carried out by the abduction of the prospective bride by the prospective groom. This issue increases the number of child marriages in West Lombok. This phenomenon has been contributing to the increasing number of child marriages in West Lombok and has become a serious issue that requires strategic breakthrough involving particular actors from various levels. Through the concept of Transnational Coalition Building, this research examines and analyzes to what extend the transnational coalition within the Yes I Do Alliance play a significant role in preventing the practice of child marriage in West Lombok. Data for this qualitative-descriptive study were gathered primarily through interviews with three individuals affiliated with each organization of the Yes I Do Alliance. Additional data were gleaned from the Baseline and Midline report of the Yes I Do program and other published literature. This study concluded that despite efforts to prevent and address child marriage in West Lombok through the transnational coalition, the scheme’s execution flaws prevented it from realizing its full potentia to achieve the maximum output. This research highlights the consequences of power imbalances that are certain and must exist in realizing a successful transnational coalition scheme. However, fundamentally this has not been accepted by the actors involved in the Yes I Do Alliance itself.